**If 2x = 3y – 5, then find the value of 8x**^{3} – 27y^{3} + 90xy + 125.

^{3}– 27y

^{3}+ 90xy + 125.

**Answer :**

Given:

2x = 3y – 5

2x – 3y = -5

Now, let us cube on both sides, we get

(2x – 3y)^{3} = (-5)^{3}

(2x)^{3} – (3y)^{3} – 3 × 2x × 3y (2x – 3y) = -125

8x^{3} – 27y^{3} – 18xy (2x – 3y) = -125

Now, substitute the value of 2x – 3y = -5

8x^{3} – 27y^{3} – 18xy (-5) = -125

8x^{3} – 27y^{3} + 90xy = -125

8x^{3} – 27y^{3} + 90xy + 125 = 0

**More Solutions:**

- Factories the following :
- Factorise 21py2 – 56py
- Factorise 2πr2 – 4πr
- Factorise 25abc2 – 15a2b2c
- Factorise 8×3 – 6×2 + 10x
- Factorise 18p2q2 – 24pq2 + 30p2q
- Factorise 15a (2p – 3q) – 10b (2p – 3q)
- Factorise 6(x + 2y)3 + 8(x +2y)2
- Factorise 10a(2p + q)3 – 15b (2p + q)2 + 35 (2p + q)
- Factorise x2 + xy – x – y
- Factorise 5xy + 7y – 5y2 – 7x